ANALYSIS REFERENCE OF GRAMMATICAL COHESION TYPES IN NAWAL EL- SADAWI’S WOMAN AT POINT ZERO - Hablil Warid; hodairiyah hodairiyah; Ach Syariful Lail (STKIP PGRI SUMENEP, 2021)
Abstract The researcher used the novel as the object of research with the title